Biology of predatory fishes in dam reservoirs and lakes - Vejřík, Lukáš (Jihočeská univerzita, 2018)
This Ph.D. Thesis is focused mainly on the biology of two typical European predatory fishes, European catfish (Silurus glanis) and perch (Perca fluviatilis). Catfish is a typical apex predator, whereas perch is a smaller species that plays role of a mesopredator. Although, catfish is the third largest freshwater fish in the world, only few studies dealing with this species have been revealed thus far. The main reason is connected with capturing of the species that is inefficient by standard ichthyologic methods. Studies, that have been revealed recently, focused mainly on expansions of catfish to the West and South Europe. Catfish is unwanted in these localities due to a potential negative impact on native fish community, thus its reduction is desirable. In contrast, catfish occurrence is important in native localities where it plays a key role as a biomanipulative species (I). Catfish is a true generalist, which is a typical feature for large-bodied apex predators connected with high energy consumption of their bodies. The second typical feature is a wide diet plasticity and thus good adaptability to new food sources. It is associated with distribution of various food sources among individuals within the population (II). By contrast, perch is one of the most studied fish in the world and hundreds of studies with IF are revealed every year. However, the more information about biology of perch have been known, the more questions have been arisen. Several phenomena are revealed also in this thesis. For instance, crucial impact of juvenile perch on the entire ecosystem is described. High predation pressure on zooplankton may induce piscivory in primarily zooplanktivorous fish (III). Further, juvenile perch utilize hypoxic pelagic zones as a refuge against predation (IV). The last surprising phenomenon is described in the study dealing with both species, catfish and perch. Their coexistence may lead in strong discrimination of one species caused by special predation that was supposed to be implausible (V).
Biology of predatory fishes in dam reservoirs and lakes
Keywords: European catfish; freshwater ecosystem; individual specialization; perch; predator-prey relationship; European catfish; freshwater ecosystem; individual specialization; perch; predator-prey relationship